2018
DOI: 10.1016/j.jsames.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric structuration onshore-offshore of the Sergipe-Alagoas passive margin, NE Brazil, based on wide-angle seismic data

Abstract: The structure and nature of the crust underlying the Camamu-Almada-Jequitinhonha-Sergipe-Alagoas basins System, in the NE Brazilian margin, were investigated based on the interpretation of 12 wide-Please note that this is an author-produced PDF of an article accepted for publication following peer review. The definitive publisher-authenticated version is available on the publisher Web site. angle seismic profiles acquired during the SALSA (Sergipe ALagoas Seismic Acquisition) experiment in 2014. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…Recall that syn-rift magmatism was contemplated by Mohriak et al (2000), as they observed thick wedges of seaward dipping reflectors on seismic profiles crossing the Sergipe-Alagoas basin. Also, recent investigations of this basin by onshore-offshore seismic refraction have found anomalously fast lower continental crust P-velocity in the necking zone (Pinheiro et al 2018), which gives further support to the occurrence of syn-rift magmatism. Another hypothesis for the fast-velocity layer under the RTJ rift basins could therefore be that syn-rift magmatic intrusions were responsible for its formation.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Recall that syn-rift magmatism was contemplated by Mohriak et al (2000), as they observed thick wedges of seaward dipping reflectors on seismic profiles crossing the Sergipe-Alagoas basin. Also, recent investigations of this basin by onshore-offshore seismic refraction have found anomalously fast lower continental crust P-velocity in the necking zone (Pinheiro et al 2018), which gives further support to the occurrence of syn-rift magmatism. Another hypothesis for the fast-velocity layer under the RTJ rift basins could therefore be that syn-rift magmatic intrusions were responsible for its formation.…”
Section: Discussionsupporting
confidence: 59%
“…The closest intrusions consist of three subparallel dolerite dykes East of the Tucano basin, with K-Ar dates of 105 ± 9 Ma, which were inferred indirectly from aeromagnetic and outcrop data (Magnavita et al 1994). Rift-related magmatism seems to be restricted to breakup along the associated marginal basins, where it has been identified as either fast-velocity (>7.0 km s -1 ) lowermost crustal bodies in refraction lines or small-volume, on-shore mafic intrusives (Blaich et al 2008;Pinheiro et al 2018).…”
Section: Stratigraphy Exhumation and Erosionmentioning
confidence: 99%
“…The graben and configuration of dikes (Figure 1), which is roughly parallel to the opening direction, and complex strata geometry with some folding, may indicate that the deformation in this segment of Potiguar involved strike‐slip to oblique tectonic component in the early rift phase. The amount of extension recorded in the grabens is comparatively minor and the average crust thickness of the segment currently above sea level is ∼35 km (Assumpção et al., 2013; Schnürle et al., 2023), that is, somewhat thicker than offshore under the shelf (Aslanian et al., 2021; Pinheiro et al., 2018). The relatively thin lithosphere is the region (Barbosa et al., 2023) may have caused that the shallow Potiguar basin is currently above sea level.…”
Section: Synrift Tectonic Structurementioning
confidence: 99%
“…In contrast, the rifted margins of the Central Segment (Figure 1) are wide (up to 600 km; Clerc et al, 2018; Contrucci et al, 2004; de Matos et al, 2021; Evain et al, 2015; Mohriak, Nemčok, et al, 2008; Moulin, 2003; Moulin et al, 2005; Péron‐Pinvidic et al, 2013, 2017; Pinheiro et al, 2018; Unternehr et al, 2010; Figure 2b). Their crustal necking domains are associated with wide distal hyperextended domains and ductilely deformed lower crust (“weak or hot margin type”; e.g.…”
Section: The South and Equatorial Atlantic Oceansmentioning
confidence: 99%